Efforts To Improve Early Reading Skills Through Picture Media In Grade I At Sdn 88 Penegah - Ana Basarum Misluna; Wyndy Sherlyna Jasmin; Salkiah Farhani; Hasrudi Adinata (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to improve students' concentration in learning through the use of images. This technique is a form of cooperative learning development that encourages thinking activities through discussion or group work. The subjects of this study were students in grade 1 at SDN 88 Penegah Sarolangun in the 2025/2026 academic year. A qualitative research approach was used, and the type of research was classroom action research (CAR). The classroom action research was conducted in two cycles. Each cycle consisted of four stages, namely: planning, implementation, observation, and reflection. Data collection techniques included tests, interviews, observation, and documentation. Based on the discussion and results of cycles 1 and 2 of the data analysis, it can be concluded that learning interest increased among first-grade students at SDN 88 Penegah by applying image media in Indonesian language learning material to improve reading skills. Learning with image media is very suitable to be applied specifically to improve students' concentration skills in Indonesian language learning.